Comparative Effects of Positional Release Technique Vs Deep Transverse Friction Massage on Pain and Disability - Ume Ammara, Fiza Shahzadi, Soyba Nazir, Kanwal Fatima, Farwah Batool, Kirran S. Gondal, M. Aqeel, Sana Shah, Sania Maqbool (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mechanical low back pain is the pain caused by natural vulnerability of the spine to static loads owing to muscular and gravity forces, as well as pain that is caused by kinetic deviation from normal physiology. Positional release technique, commonly known as strain counterstrain (SCS), is a passive positional therapy that uses indirect hand manipulation to reduce musculoskeletal discomfort and dysfunction. Aim: To compare the effects of positional release therapy and deep transverse friction massage on lumbar pain, lumbar range of motion and disability among patients with mechanical low back pain Methods: After getting ethical approval from the University of Faisalabad, 40 male and female mechanical low back pain patients aging 20-40 years, having at least one trigger point in the iliopsoas muscle on the anterior lumbar aspect were recruited in the study bu purposive sampling, and were randomly allocated into 2 groups by means of lottery method. The outcome measures were assessed at three different occasions i.e. baseline, 2nd week and 4th week. The numeric pain rating scale for lumbar pain, goniometry for lumbar range of motion and oswestry disability scale for lumbar disability were used in the study. Results: A total of 40 participants were included of which 57.5 % were male and 42.5% were females. The mean age was 30.37±6.01 years, mean BMI was 24.94 ± 3.64. 2 participants from positional release group and 1 from deep transverse friction massage were dropped out. NPRS showed 3.27 and 3.05 decrease, lumbar flexion showed 11.28 and 11.42 degrees increase, lumbar extension showed 4.9 and 4.94 degrees increase and ODI showed 14.53 and 14.78 points decrease in positional release technique and deep transverse friction massage, respectively. Conclusion: Both the techniques produced significant results in reducing lumbar pain, the lumbar disability and improving lumbar range of motion in their respective group, but none of them proved to be superior to other in between group comparison. Keywords: Deep Transverse Friction Massage; Mechanical Low Back Pain; NPRS; Positional Release Technique.